Intracellular mechanisms of l-selectin induced capping - Junge, Sonja Angela; Donner, Birgit Cornelia; Lepple-Wienhues, Albrecht; Nilius, Bernd; Lang, Florian; Linderkamp, Otwin; Gulbins, Erich (Cellular signalling, 1999)
Leucocyte adhesion to endothelial cells is a tightly regulated process involving selectins, integrins and immunoglobulin-like proteins. Cell adhesion and communication are controlled by membrane dynamics like receptor capping. Capping of surface receptors is an ubiquitous mechanism but still not well understood. Employing immunofluorescence techniques, we demonstrate that l-selectin triggering results in receptor capping of the l-selectin molecules in lymphocytes. Using pharmacological inhibitors and genetic deficient cell lines we show that this process involves intracellular signalling molecules. l-Selectin capping seems to be independent on activation of p56lck-kinase, but requires the neutral sphingomyelinase, small G proteins and the cytoskeleton. Therefore, capping of l-selectin upon stimulation might play an important role in the very early phase of lymphocyte trafficking.